#TITLE_ALTERNATIVE# - SUHARA SIANIPAR (NIM 13204168), ROMMEL
Ground Penetrating Radar (GPR) is one of the application development of radar. Like other common radar system, Antenna is one of the important part in GPR. The writer simulates antenna which can be used for transmitting 1.6 ns pulse in this Final Project. The duration of this pulse is in a middle range frequency that can be used for archeologic use and concrete inspection. The proposed antenna is dipole antenna. This dipole antenna equipped with 655 resistive loading and 6 layered dielectric slabs. Resistif loading is used to minimize ringging and layered dielectric slab is used as transition for electromagnetic waves to travel from antenna to medium to maximize signals amplitude that detected in the medium. Resistive loads are based on Wu-King profile, and the εr of layered dielectric slabs are based on linear profile. The thickness of each layer is constant. The reason of these configuration is because of the simplicity. Parameter which will be analyzed in this Final Project are main pulse and ringing peak to peak amplitude, input impedance and VSWR. For electromagnetic analysis in time domain we use FDTD (finite-difference time-domain) method with FDTD3D software to measure transmitted waveform in time domain. To obtain input impedance and VSWR, we use Matlab to process data from FDTD.